A case of impetigo herpetiformis in which termination of pregnancy was required. Issue 7 (July 2020) - Yao, Xinjing; Zhang, Xiaoxia; Peng, Min; Wang, He; Meng, Yizi; Chen, Ying
Impetigo herpetiformis is a rare variant of generalized pustular psoriasis that occurs during pregnancy or is triggered by pregnancy, often in association with hypocalcemia. This condition is associated with increased maternal and fetal morbidity and mortality. We report a 29-year-old pregnant woman who presented to hospital at the gestational age of 20 weeks with widespread erythema covered with pustules that coalesced to form lakes of pus. She did not respond to corticosteroids, immunosuppressants, or phototherapy. Finally, intra-amniotic injection of ethacridine lactate was administered to terminate the pregnancy, and the patient showed complete recovery in 3 months. Insight from this case report may facilitate optimal management of this relatively rare entity.